Establishing the project management maturity model and performance of GDID Maintenance teams in academic hospitals - Kepadisa, Thebe Kabo (My University, 2017)
ABSTRACT This study seeks to establish the PMM level of the GDID maintenance teams based at the 5 academic hospitals around Gauteng province. Then the study will also investigate the association of PMM level to project performance and business performance of the GDID maintenance teams. While GDoH’s primary goal is to render health care services to the community, GDID’s directive is to ensure that the health facilities are maintained properly and in a functional state. Therefore, GDID maintenance teams execute mandates that are turned into projects to maintain and improve the functionality of the health facilities. A survey was conducted on 70 GDID employees carrying out project implementation based in 5 Academic hospitals, namely CHBAH, CMJAH, DGMAH, SBAH and TMRH. About 53 employees returned the survey questionnaires and 50 of the answered questionnaires were usable. Data was ran on SAS and results were analysed. The PMM level for CHBAH, CMJAH and SBAH is 3, for DGMAH is 2 and for TMRH is 4. The radar chart showed the 4 academic hospitals to resemble octagon on the PMM knowledge management area except for DGMAH. The study revealed that high levels of PMM are not associated with project performance for all academic hospitals, the study further revealed high levels of PMM are also not associated with business performance except for DGMAH where high levels of PMM will improve business performance. These results will help and equip project managers with insight to know which knowledge management areas of PMM will they need to improve on.
M.B.A. Thesis
Keywords: Project management -- South Africa, Hospitals -- Administration.